A Holistic Examination of the Geotechnical Design of Longwall Shields and Associated Mining Risks - Russell C. Frith (International Conference on Ground Control in Mining, 2013)
This paper examines the design of longwall shields, focusing on those aspects that are critical to either their successful application or contribution to failure during longwall extraction. In many instances, longwall shields are assessed and designed along lines similar to that of roadway ground support systems, namely according to typical or normal geotechnical conditions. However it will be contended that for longwall shields, this is inappropriate because unlike roadway ground support systems, longwall shields cannot be supplemented with additional or secondary support in localised areas of adverse geotechnical conditions. In other words, the longwall shield needs to be designed according to what are judged to be worst case or adverse geotechnical conditions?the outcome being that a well-designed shield will be significantly over-rated for the majority of its working life. Therefore, it will be argued that the additional capital cost of such shield design can be readily justified as a prudent riskbased outcome that is essential to minimising future business risks due to strata instability on the longwall face. Shield geometry will be discussed, including such relevant factors as leg angle, inclination of the top caving shield, canopy ratio, operating height range, and tip to face distance. These are all well-established longwall shield design considerations and, most importantly, areas whereby inadequate design can render a longwall shield as highly ineffective. The issue of tip to face distance will be considered in detail, in particular, the extent by which it is an important geotechnical design consideration, the conclusion being reached that, in fact, it is not. The critical importance of maximising set to yield ratio within practical operating limits will be justified, the wisdom of this having been subject to questioning in more recent technical literature. Overall, the aim is to provide the industry with a set of suggested guidelines for future use when designing longwall shields and, hopefully, to initiate discussion on a subject that, unlike roadway ground support design, is not well covered in its entirety in the published technical literature.